Parent-offspring resemblance for educational attainment reduces with increased social class in a global sample: evidence for the compensatory advantage hypothesis - Woodley of Menie, Michael A.; Sarraf, Matthew A.; Peñaherrera-Aguirre, Mateo; Rindermann, Heiner (Frontiers in Psychology, 2024)
Introduction The degree to which (self-reported) social class predicts parent-offspring resemblance for educational attainment (EA) is examined in a globally representative dataset of 69,116 individuals sourced from 56 countries. Methods A hierarchical general linear model is used to predict participant EA with the two-way interaction between class and parental EA, after controlling for regional effects, the main effects of age, class, parental EA, and interactions among these. Results Social class-by-parental EA interaction negatively predicts participant EA (semipartial r = −0.04, 95% CI = −0.05 to −0.03), meaning that among those who report belonging to a “higher” social class, the degree of parent-offspring resemblance for EA is reduced, contrary to the Scarr-Rowe hypothesis, which holds that genetic influences on cognitive ability and related phenotypes (captured here in part by parent-offspring resemblance) should be greater among those from higher socioeconomic status (SES) backgrounds. These results replicate using a quantile regression model, where it was found that among those with lower social class ordinals, the strength of the parent-participant EA association is significantly stronger relative to those in the highest ordinal. No significant sex differences are present. Discussion These findings are consistent with the compensatory advantage hypothesis, which predicts decreased heritability of EA and related phenotypes among affluent families, as increased access to educational resources should enhance opportunities for cognitive growth in a way that compensates for intrinsic disadvantages.